Analisis Sentimen AFC U23 Asian Cup 2024 menggunakan Algoritma Nave Bayes - kurniawan, muhammad arif; Yuniarti, Angger Styo; makin, samsul (Universitas Insan Pembangunan Indonesia, 2024)
The AFC U-23 Asian Cup is a very important football tournament watched by millions of fans across Asia and the world. Sentiment analysis of these events can provide insight into how the public feels and opinions towards the matches, teams and players, which can be very beneficial for organizers, sponsors and the media. This research uses the Nave Bayes algorithm to group words from the Twitter application with the aim ofprovide a significant contribution to the understanding of public perception and fan involvement in major sporting events such as the AFC U-23 Asian Cup 2024. The results of this research withusing the Nave Bayes algorithm to analyze public opinion regarding the 2024 AFC U-23 Asian Cup gave an accuracy value of 78%. These results show that the Nave Bayes model has quite good performance in carrying out sentiment analysis.Keywords: AFC U-23 Asian Cup 2024, Sentimen, Nave Bayes, Twitter